Assessment of Water Quality in Groundwater, Surface and Spring Water in Phosphorite Mining Area of Tebessa (Algeria) - Boumaza, Bilal; Chekushina, Tatiana V.; Vorobyev, Kirill A.; Schesnyak, Leonid E. (Journal of Environmental Accounting and Management, 2026)
Industrial discharges of phosphate constitute an enormous danger for the environment, because of their high content of heavy metals, which causes contamination of water and soil. The current study aims to measure the trace metal pollution (Al, Cr, As, Se, U, Fe, Si, Sr, Li, Zn, Pb, Ni, and Cu) in surface waters, spring waters and groundwater found in the Djebel Onk. Phosphate treatment Area in order to assess the magnitude of the risk on the health of the people. Thus, samples were analyzed using the Inductively Coupled Plasma Mass Spectrometry method. The results show that the surface water, spring waters, and groundwater are contaminated by these trace metals, particularly lead, uranium, iron, lithium, selenium, and magnesium. It has been observed that the average maximum levels in groundwater are iron 24.32 mg/l, uranium 0.0017 mg/l, selenium 0.0365 gm/l, lithium 0.05 mg/l, lead 0.037 mg/l, while in surface waters, the maximum iron content of 1.1565 mg/l, uranium of 0.021 mg/l, selenium of 0.021 gm/l, lithium of 0.327 and lead of 0.05 mg/l were observed, in spring waters the maximum iron, selenium and lead levels are 0.225 mg/l, 0.017mg/l, 0.031gm/l respectively, which are higher than the World Health Organization standard for drinking water. The consumption of these waters without treatment could have negative impacts on human health in general and that of children in particular.